2021
DOI: 10.1124/dmd.121.000442
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Metabolites as Inhibitors of Major Hepatic CYP450 Enzymes, with Implications for Cannabis-Drug Interactions

Abstract: The legalization of cannabis in many parts of the United States and other countries has led to a need for a more comprehensive understanding of cannabis constituents and their potential for drug-drug interactions. Although (−)- trans -Δ 9 -tetrahydrocannabinol (THC), cannabidiol (CBD), and cannabinol (CBN) are the most abundant cannabinoids present in cannabis, THC metabolites are found in plasma at higher concentrations and for a longer duration than that of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 49 publications
(80 reference statements)
0
94
0
Order By: Relevance
“… a The recommendations for the management of each interaction are according to the level of the clinical relevance of cannabis–drug interactions [ 8 , 9 , 10 ]. In addition, some information stated by the authors was included.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… a The recommendations for the management of each interaction are according to the level of the clinical relevance of cannabis–drug interactions [ 8 , 9 , 10 ]. In addition, some information stated by the authors was included.…”
Section: Figurementioning
confidence: 99%
“…Cannabinoids, especially CBD, are metabolized by isoenzymes of the family CYP, which can lead to interactions between a cannabis base extract and other drugs. In this way, recent in vitro studies have shown that: THC competitively inhibits the enzymes CYP1A2, CYP2B6, CYP2C9, and CYP2D6; CBD competitively inhibits the enzymes CYP3A4, CYP2B6, CYP2C9, CYP2D6, and CYP2E1; and cannabinol (CBN) competitively inhibits the enzymes CYP2B6, CYP2C9, and CYP2E1 [ 9 ]. By contrast, drug interactions due to pharmacodynamic mechanisms are generally less common [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Duloxetine (several drugs in other fields; propofol, anticoagulants!) in vitro: inhibition of several CYP enzymes by cannabinoids and main metabolites, including CYP 2B6, 2C9, 2D6; minor inhibition: 1A2, 2C19, 3A4 [60,62] Several drugs, including opioids, NSAIDs and possibly cyclosporine and tacrolimus (CBD) [63] anticholinergic agents (risk of tachycardia) (several drugs in other fields)…”
Section: Cannabis Sativamentioning
confidence: 99%
“…Cannabinoids are substrates of CYP3A4 and 2C9. In vitro data suggest the influence of cannabinoids and their metabolites on several CYP 450 enzymes [ 62 , 124 ]. The strongest effects were CYP2C9, 2B6, and 2D6 inhibition, but CYP 1A2, 2C19, and 3A4 might be affected as well.…”
Section: Assessment Of Herbal Drugs and Their Interactionsmentioning
confidence: 99%
“…Cannabinoid Cannabinoid Effect Anesthetic CYP2B6 THC, CBD THC and CBD both are inhibitors [300] Propofol [301], Ketamine [302,303] CYP2C9 THC, Cannabinol [304] THC as inhibitor [300,305] Propofol [301], Ketamine [302,303], Rocuronium [306] CYP2E1 THC metabolites, CBD Competetive inhibition [300] Halothane [307], Isoflurane [307], Sevoflurane [307], Enflurane [307], Desflurane [307,308] CYP3A4 THC, CBD, Cannabinol CBD is an inhibitor [300,309] Ketamine [302], Midazolam [310], Diazepam [311], Fentanyl [312], Rocuronium [306], Codeine [307,313], Propofol [301], Acetaminophen [314] CYP2A6 THC Genotype-dependent [295] Dexmedetomidine [315] CYP2C19 THC, CBD THC and CBD are both inhibitors [309] Diazepam [311], Rocuronium [306] CYP1A1/2 CBD CBD is an inducer [309] Diazepam [311] CYP2D6 THC, CBD THC and CBD are both inhibitors [300] Tramadol [316], Codeine [314,317], Oxycodone [314,318], Hydrocodone…”
Section: Cytochromementioning
confidence: 99%